Epitope mapping of inhibitory antibodies targeting the C2 domain of coagulation factor VIII by hydrogen–deuterium exchange mass spectrometry. (December 2013) - Sevy, A. M.; Healey, J. F.; Deng, W.; Spiegel, P. C.; Meeks, S. L.; Li, R.
Summary Background The development of anti‐factor VIII antibodies (inhibitors) is a significant complication in the management of patients with hemophilia A, leading to significant increases in morbidity and treatment cost. Using a panel of mAbs against different epitopes on FVIII, we have recently shown that epitope specificity, inhibitor kinetics and time to maximum inhibition are more important than inhibitor titer in predicting responses to FVIII and the combination of FVIII and recombinant FVIIa. In particular, a subset of high‐titer inhibitors responded to high‐dose FVIII, which would not be predicted on the basis of their inhibitor titer alone. Thus, the ability to quickly map the epitope spectrum of patient plasma with a clinically feasible assay may fundamentally change how clinicians approach the treatment of high‐titer inhibitor patients. Objectives To map the epitopes of anti‐FVIII mAbs, three of which are classic inhibitors and one of which is a non‐classic inhibitor, by the use of hydrogen–deuterium exchange coupled with mass spectrometry (HDX‐MS). Methods The binding epitopes of four mAbs targeting the FVIII C2 domain were mapped with HDX‐MS. Results The epitopes determined with HDX‐MS are consistent with those obtained earlier through structural characterization and antibody competition assays. In addition, classic and non‐classic inhibitor epitopes could be distinguished by the use of a limited subset of C2 domain‐derived peptic fragments. Conclusion Our results demonstrate the effectiveness and robustness of the HDX‐MS method for epitope mapping, and suggest a potential role of rapid mapping of FVIII inhibitor epitopes in facilitating individualized treatment of inhibitor patients.